FENOMENA AKIBAT LEMAHNYA PROGRAM PERAWATAN DALAM OPERASI PERANGKAT LISTRIK - Achmad Suntoro (BATAN, 2011)
Som e experiences on repai ring of many electrical equipment have given some practical knowl edges that how important of a mai ntenance program to be conducted continuously. Three examples of practical phenomena on lack of maintenance program and the necessity of measurement usi ng a correct tool as well as an example of how to define the poi nts of locationunder surveilance of predicti ve maintenace program using FTA (Fault ree Analysis) will be discussed i n thi s paper.These exampl es are the evidence and information (facts) that maintenance program and utilizing an apt measurement tool are absol utel y necessary to be conducted to mai ntai n the reliability of equipment as well as install ation. FTA technique i s not onl y used at a design phase but also can be used at planning and mai ntenace activities. Pengalaman dalam memperbaiki perangkat li strik tel ah memberi pelajaran praktis akan perlunya program perawatan diterapkan secara kontinyu. Tiga contoh fenomena praktis akibat l emahnya perawatan dan perlunya alat ukur, serta sebuah contoh cara menentukan titi k-titikposisi perawatan-prediktiff menggunakan FTA (Fault Tree Analysis) ibahas dalam makal ah ini . Contoh-contoh tersebut merupakan bukti dan informasi (fakta) bahwa perawatan dan penggunaan alat ukur yang tepat mutlak harus dit erapkan untuk menjaga keandalan operasi sistem perangkat maupun instal asi. Teknik FTA bukan hanya dapat di gunakan pada fase disain, tapi juga dapat digunakan pada perencanaan perawatan